Molecular identification of Chinese citrus fly, Bactrocera minax (Diptera: Tephritidae) in Nepal - Adhikari, Debraj; Thapa, Resham B; Joshi, Samudra L; Du, Jason J; Raut, Roji; Manandhar, Prajwal; Rajbhandari, Pragun; Karmacharya, Dibesh (Nepal Journal of Science and Technology, 2023)
An accurate identification at the species level is often the first step in successfully controlling, mitigating and managing of insect pests. Species identification utilizing molecular approaches can complement morphological identification, often resulting more accurate result. Tephritid fruit fly insects can be identified quickly using DNA barcoding technology. In this study, Chinese fruit fly (Bactrocera minax), a destructive citrus pest collected in Nepal, was identified using barcoding method with the sequence of mitochondrial cytochrome c oxidase I (COI) gene.